Six sigma methodologies: implementation and impacts on Portuguese small and medium companies (SMES) - Fonseca, Luís (2014)
Abstract: Six Sigma is a disciplined approach for dramatically reducing defects and producing measurable financial results (Anand, 2006; Linderman et al. 2003). It should not be a simple statistical tool, but rather a strategic management approach by supporting key projects aligned with the business goals and customer requirements. Although associated with considerable Return on Investments, there is not enough evidence of Six Sigma application within Portuguese companies. It is the aim of this exploratory research to study Six Sigma utilization by Portuguese Small and Medium Enterprises (SMEs). The descriptive analysis and the statistical tests carried out, point to lack of knowledge with this Methodology (Higher at Top Management level) and a sense of comfort with the existing management systems (mainly ISO 9001). The authors recommend increasing Six Sigma training and education and additional studies to gather further knowledge and contribute to more competitive and sustainable organizations.